Conductive TiC/Ti–Cu/C composites fabricated by Ti–Cu alloy reactive infiltration into 3D-printed carbon performs. (July 2015) - Rambo, Carlos R; Travitzky, Nahum; Greil, Peter
The microstructure and electrical properties of dense TiC/Ti–Cu/C composites fabricated by pressureless reactive infiltration of Ti–Cu alloy into porous starch-derived carbon preforms prepared by 3D printing was evaluated. Porosities in the range of 65–78 vol% were varied by post-isostatic pressing the as-printed preforms at pressures of 50–400 MPa. The reactive melt infiltration was carried out at 1100℃ in a flowing Ar atmosphere and resulted in formation of a composite comprised predominantly of substoichiometric TiC, binary intermetallic Ti–Cu phases and residual carbon. Scanning electron microscopy analyses revealed a microstructure consisting of dispersed fine-grained TiC in a Ti–Cu matrix surrounded by a continuous carbon phase. Electrical resistivity measurements using the four-probe method were carried out and correlated to the composite microstructure. The electrical resistivity was evaluated in terms of carbon and TiC volume fractions.